Enhancing rufomycin production by CRISPR/Cas9-based genome editing and promoter engineering in Streptomyces sp. MJM3502 - Chun Su; Nguyen-Quang Tuan; Wen-Hua Li; Jin-Hua Cheng; Ying-Yu Jin; Soon-Kwang Hong; Hyun Lee; Mallique Qader; Larry Klein; Gauri Shetye; Guido F. Pauli; Scott G. Flanzblau; et al. (Synthetic and Systems Biotechnology)
Streptomyces sp. MJM3502 is a promising producer of rufomycins, which are a class of potent anti-tuberculosis lead compounds. Although the structure, activity, and mechanism of the main rufomycin 4/6 and its analogs have been extensively studied, a significant gap remains in our understanding of the genome sequence and biosynthetic pathway of Streptomyces sp. MJM3502, and its metabolic engineering has not yet been reported. This study established the genetic manipulation platform for the strain. Using CRISPR/Cas9-based technology to in-frame insert the strong kasO∗p promoter upstream of the rufB and rufS genes of the rufomycin BGC, we increased rufomycin 4/6 production by 4.1-fold and 2.8-fold, respectively. Furthermore, designing recombinant strains by inserting the kasO∗p promoter upstream of the biosynthetic genes encoding cytochrome P450 enzymes led to new rufomycin derivatives. These findings provide the basis for enhancing the production of valuable natural compounds in Streptomyces and offer insights into the generation of novel active natural products via synthetic biology and metabolic engineering.